2015
DOI: 10.4204/eptcs.180.5
|View full text |Cite
|
Sign up to set email alerts
|

Adaptive Homing is in P

Abstract: Homing preset and adaptive experiments with Finite State Machines (FSMs) are widely used when a non-initialized discrete event system is given for testing and thus, has to be set to the known state at the first step. The length of a shortest homing sequence is known to be exponential with respect to the number of states for a complete observable nondeterministic FSM while the problem of checking the existence of such sequence (Homing problem) is PSPACE-complete. In order to decrease the complexity of related p… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
3
3
1

Relationship

3
4

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 15 publications
0
5
0
2
Order By: Relevance
“…Адаптивная установочная последовательность может быть построена по соответствующему установочному автомату [28,31], и далее мы адаптируем данный подход к синтезу кратчайшей временной адаптивной установочной последовательности для автомата с временными ограничениями S на основе конечно-автоматной абстракции.…”
Section: синтез адаптивных временных установочных последовательностейunclassified
“…Адаптивная установочная последовательность может быть построена по соответствующему установочному автомату [28,31], и далее мы адаптируем данный подход к синтезу кратчайшей временной адаптивной установочной последовательности для автомата с временными ограничениями S на основе конечно-автоматной абстракции.…”
Section: синтез адаптивных временных установочных последовательностейunclassified
“…As each synchronizing test case is a homing test case with additional constraints, the existence check as well as the derivation of such test cases relies on such procedures for homing test cases. In (Kushik and Yevtushenko, 2015), it has been shown that when each state of a complete observable nondeterministic FSM can be initial, the existence of a homing test case can be checked in polynomial time. The procedure for deriving such test cases and potential heuristics improving the performance of the corresponding algorithm are discussed in (Kushik and Yenigun, 2015).…”
Section: Reducing the Length Of Synchronizing Test Cases For Nondetermentioning
confidence: 99%
“…Not (Kushik and Yevtushenko, 2015). Represent them as as tree-like FSMs (where only the leaf nodes are allowed to have an indegree greater than 1) with terminal nodes r 1 , …, r n and designated deadlock state D, such that there exists a trace γ from the initial state of R jk to state r j if and only if {r j } is the γ-successor of the pair {s j , s k }.…”
Section: Reducing the Length Of Synchronizing Test Cases For Nondetermentioning
confidence: 99%
See 1 more Smart Citation
“…In this section, we discuss how to optimize the procedure for deriving an adaptive HS for an observable FSM S. The procedure is taken from [9] while the complexity of the related problem is given in [15]. The homing test case derivation strategy is based on the condition that each state pair of S is adaptively homing.…”
Section: Minimizing Adaptive Hs For Nondeterministic Fsmsmentioning
confidence: 99%